Analysis of Factors Affecting Compliance Treatment of Pulmonary Tuberculosis Patients in the Work Area - Bazikho, Senang Hati; Amirah, Asriwati; Nasution, Miskah Afriani; Hutajulu, Setia Megawati; Muflih, Muflih (Journal of Community Health Provision, 2025)
Pulmonary tuberculosis (TB) is a disease infectious direct and is threat big for development source Power man so that need get more attention​ Serious from all parties. As for objective in study This is for analyze factor affecting​ compliance treatment Pulmonary Tuberculosis Patients in the Work Area Service Health Regency South Nias 2024. Regency South Nias has amount cases of pulmonary TB that every the year experience improvement, so that own potential height non-compliance patient in run Pulmonary TB treatment. Type study This use design study quantitative with cross sectional study approach. Sample in study This totaling 72 respondents Pulmonary TB sufferers in the Work Area Service Health Regency South Nias 2024. Based on results analysis that knowledge (p=0.003), duration of treatment (p=0.000), supervisor swallow drug (PMO) (p=0.000) there is influence support family (p=0.000) has influence to compliance Pulmonary Tuberculosis Treatment in Work Areas Service Health Regency South Nias 2024. As for the suggestions in study This expected to officer health For give counseling to TB patients under surveillance family (PMO) towards compliance treatment patient Pulmonary tuberculosis is complete appropriate on time.